Functionalized styrene synthesis via palladium-catalyzed CC cleavage of aryl ketones. (13th April 2022) - Zhang, Xu; Wang, Zhen-Yu; Wang, Xing; Xu, Hui; Dai, Hui-Xiong
Graphical abstract: Abstract: We report herein the synthesis of functionalized styrenes via palladium-catalyzed Suzuki–Miyaura cross-coupling reaction between aryl ketone derivatives and potassium vinyltrifluoroborate. The employment of pyridine-oxazoline ligand was the key to the cleavage of unstrained CC bond. A variety of functional groups and biologically important moleculars were well tolerated. The orthogonal Suzuki–Miyaura coupling demonstrated the synthetic practicability.